Tests of the Oddity Effect Hypothesis in mixed-species parid flocks - Zaharia A. Selman; Eric K. Frazier; Colton B. Adams; Todd M. Freeberg (PLoS ONE, 2026)
Although there are major benefits of group membership, there might be severe costs to being in a group for phenotypically rare individuals. Whereas the role of rarity in antipredator behavior is well-documented in fish species, there is little empirical evidence on how rarity affects this behavior within mixed-species avian groups. Understanding this is important for clarifying how various antipredator behaviors function in different social contexts. The Oddity Effect Hypothesis predicts that predators will choose phenotypically rare individuals within groups, and as a response to their oddity, these prey individuals should behave as inconspicuously as possible, often by delaying signaling. Here we examined the role of rarity in data taken from and analyzed separately in two different, published, field experiments. We measured the latency to call in mixed-species flocks with one versus two or more individuals of Carolina chickadees ( Poecile carolinensis ), tufted titmice ( Baeolophus bicolor ), or white-breasted nuthatches ( Sitta carolinensis ) after a predator model was presented. We also tested two alternative hypotheses, the ‘probability of calling’ and ‘recruitment’ hypotheses. In support of the Oddity Effect Hypothesis, we found evidence that single individuals took longer to call: chickadees in the first experiment, using a screech owl ( Megascops asio ) model, and titmice and nuthatches in the second experiment, using a Cooper’s hawk ( Accipiter cooperii ) model. For our alternative hypotheses, we found no evidence of shorter call latencies with more conspecifics in flocks due to simple probabilities of calling and no evidence of shorter calling latencies with fewer conspecifics due to increased motivation to recruit conspecifics. Our results lend support to the Oddity Effect Hypothesis, though we urge caution due to our small sample sizes.